Reforming the Tourism Promotion Board for an Effective Tourism Promotion in Indonesia: A Legal Perspective - Anak Agung Gede Duwira Hadi Santosa; Putu Devi Yustitia Utami; I Made Marta Wijaya (Center for Southeast Asian Social Studies (CESASS), 2021)
The Indonesia/Regional Tourism Promotion Board (or I/RTPB) is an agency having duties to assist the development of the tourism sector. Since its establishment, it has not been able to play an optimal role in performing its duties and responsibilities. The purpose of this study is to find out and understand the institutional arrangements for the I/RTPB in the current legislation and to find out and formulate the ideal form of the I/RTPB in accelerating its functions especially for the recovery of the tourism sector in the post-pandemic context. This article uses a doctrinal research method with a statutory approach. The study shows the problem of the provisions on the I/RTPB in the Tourism Law in Chapter X from Article 36 to Article 49. To properly function for the economic recovery after the pandemic, there is a need to restructure the I/RTPB as an independent body with a mandate in the field of tourism promotion.